2020
DOI: 10.2991/efood.k.200812.001
|View full text |Cite
|
Sign up to set email alerts
|

Oral Administration of Oyster Peptide Prevents Bone Loss in Ovariectomized Mice

Abstract: Osteoporosis is a disordered metabolic disease occurred congenitally or secondary. Although peptide agents have been approved to prevent osteoporosis administrated through subcutaneous injection, rare reports focused on peptide oral administration for preventive purpose. An eight peptide, P-CG-01 (YRGDVVPK) derived from oyster protein hydrolysates in gastrointestinal tract can promote the proliferation of osteoblast in vitro. In this study, ovariectomized mouse model was used to investigate the osteogenesis ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 49 publications
(54 reference statements)
2
9
0
Order By: Relevance
“…Previous studies reported that some bioactive peptides and proteins, such as peptide FBP-KSA, P-CG-01, and lactoferrin, exhibited strong proliferation activity of osteoblasts by increasing the phosphorylation level of major proteins in the MAPK pathway. 11,53,54 Sea cucumbers were rich in collagen; it has been reported that peptides derived from mahi mahi bone collagen upregulated osteogenesis also through activating Runx2 via the p38 MAPK signaling pathway, which was consistent with our results. 55 SJP Promotes Bone Formation in Vivo.…”
Section: ■ Results and Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Previous studies reported that some bioactive peptides and proteins, such as peptide FBP-KSA, P-CG-01, and lactoferrin, exhibited strong proliferation activity of osteoblasts by increasing the phosphorylation level of major proteins in the MAPK pathway. 11,53,54 Sea cucumbers were rich in collagen; it has been reported that peptides derived from mahi mahi bone collagen upregulated osteogenesis also through activating Runx2 via the p38 MAPK signaling pathway, which was consistent with our results. 55 SJP Promotes Bone Formation in Vivo.…”
Section: ■ Results and Discussionsupporting
confidence: 92%
“…Compared with the cells treated with SJP + inhibitors, the phosphorylation levels of JNK, ERK, and p38 MAPK in the SJP (100 μg/mL) treatment group were significantly increased, and the activation effect of ERK was the most significant, indicating that the MAPK pathway was involved in regulating the proliferation of osteoblasts by SJP (Figure B). Previous studies reported that some bioactive peptides and proteins, such as peptide FBP-KSA, P-CG-01, and lactoferrin, exhibited strong proliferation activity of osteoblasts by increasing the phosphorylation level of major proteins in the MAPK pathway. ,, Sea cucumbers were rich in collagen; it has been reported that peptides derived from mahi mahi bone collagen upregulated osteogenesis also through activating Runx2 via the p38 MAPK signaling pathway, which was consistent with our results …”
Section: Resultssupporting
confidence: 92%
“…Many studies have found that algae, fish, shellfish, and other marine resources include marine bioactive compounds with substantial bone metabolism regulating functions. 10–12 Seafood bioactive peptides can regulate bone growth by modulating numerous signaling pathways and have great potential in the development of food and pharmaceuticals for osteoporosis management. 13 Previous studies have shown that calcium binding peptides from Pacific cod bone could markedly reduce the TRAP5b activity in serum of ovariectomized mice, which has potential anti-bone resorption activity.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, investigation of the temporary functional stability and sensitivity to temperature of Zn‐chelating hydrolysates in the aqueous phase is necessary. Moreover, the GI stability of hydrolysates also contributes to the continuous intestinal absorption 7 . Based on the structures of peptides, they might arrive at the small intestine or even transport into the blood system intact or GI proteases‐degraded form, 8 which is associated with the physical and biochemical conditions (such as the pH level, as well as pepsin and pancreatin) in the GI system.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the GI stability of hydrolysates also contributes to the continuous intestinal absorption. 7 Based on the structures of peptides, they might arrive at the small intestine or even transport into the blood system intact or GI proteasesdegraded form, 8 which is associated with the physical and biochemical conditions (such as the pH level, as well as pepsin and pancreatin) in the GI system. The most vulnerable parameters of peptides that are sensitive to GI condition is the alteration of molecular distribution, which might affect the metal-chelating ability and even the bioaccessibility of the metal in the human GI system.…”
Section: Introductionmentioning
confidence: 99%